The Effect of Enhancing Unemployment Benefits in Korea: Wage Replacement Rate vs. Maximum Benefit Duration - Jiwoon Kim (KDI Journal of Economic Policy, 2018)
This paper studies the macroeconomic effects of an enhancement in unemployment benefits in Korea. In particular, I quantify the welfare effect of two specific policy chances which have been mainly discussed among policymakers in recent years: increasing wage replacement rates by 10%p and extending maximum benefit durations by one month. To this end, I build and calibrate an overlapping generation model which reflects the heterogeneity of the unemployed and the specificity of the unemployment insurance (UI) system in Korea. The quantitative analysis conducted here shows that extending maximum benefit durations by one month improves social welfare, whereas increasing wage replacement rates by 10%p deteriorates social welfare. Extending maximum benefit durations is applied to potentially all the UI recipients, including unemployed workers whose wage before job loss is relatively low and whose marginal utility is relatively high. However, increasing wage replacement rates is applied to only a small number of UI recipients whose wage before job loss is relatively high, while the increase in the UI premium is passed onto all of the employed. This study suggests that given the current UI system and economic environment in Korea, it is more desirable to extend maximum benefit durations rather than to increase wage replacement rates in terms of social welfare.
Keywords: E24; J64; J65; 330; Unemployment Insurance; Unemployment Benefits; Wage Raplacement Rate; Maximum Benefit Duration